THU0611 Long-term follow-up of 269 children born to mothers with systemic autoimmune diseases: a national survey from 24 rheumatology centers. (15th June 2017) - Nalli, C; Andreoli, L; Carini, C; Rodrigues, M; Dall'Ara, F; Lazzaroni, MG; Bartoloni-Bocci, E; Chighizola, CB; Campochiaro, C; Conigliaro, P; Corrado, A; D'Angelo, S; et al.
Abstract : Background: Rheumatic diseases (RD) affect women during reproductive age. Children's outcome is a major topic for counselling on family planning, but no large studies are available. Objectives: We aimed at assessing the long-term health conditions of children born to mothers with RD through a self-reported questionnaire. Methods: 24 Rheumatology Centers distributed the questionnaire (65 multiple choice and 12 open-answer questions) to consecutive women with RD attending their outpatient clinic during September 2015. Data were compared according to maternal diagnosis (MD) -chronic arthritis (CA) or connective tissue disease (CTD)- and to the timing of pregnancy (before or after MD of RD). Results: The survey yielded data about 269 children born to 184 mothers (63 CA, 121 CTD). According to MD, children had a mean age of 17.1 (±9.6 SD) and 14.4 (±9.0 SD) years at the time of interview, and male children were 52/93 (56%) and 91/176 (52%), respectively. Twenty-nine children in the CA group (31.2%) and 64 in the CTDs group (36.4%) were born after MD of RD. Pre-term delivery (before 37 weeks) was observed in 48 cases (17.8%), mostly children born to mothers with CTD (37/48, 77%). Regarding school performance, 12 children (4.5%) repeated one year of school, in 7 cases for indolence, in 3 for learning disabilities (LD)/health problems (HP), in 2 for family problems. Eleven of these children were born before MD. Overall, 9 children (3.3%) were diagnosed with a LD and 53 children were affected by HP requiring either hospitalization or evaluation by a Specialist (Table). Three children (1%) were affected by autoimmune disease. Conclusions: The long-term follow-up of children born to women with RD is reassuring of an outcome similar to that of the general pediatric population (GPP). Autoimmune diseases are not frequent. Problems seem to cluster in children born to CTD, especially after MD, with a higher frequency of LD (6.3% vs 2.5–3.5% of GPP), but no particular pattern of exposure to maternal autoantibodies nor drugs was observed. Acknowledgements: Statistical analysis supported by an unrestricted grant by UCB Pharma Thanks to Patients Associations and Participants to the survey Disclosure of Interest: None declared